2014
DOI: 10.1044/gics4.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Cluttering Treatment: Theoretical Considerations and Intervention Planning

Abstract: This article presents a variety of treatment approaches based on an understanding of four components of communication, and describes cluttering intervention focusing on problem identification, speech rate reduction, appropriate pausing, appropriate monitoring, and addressing story narrating skills. Therapeutic considerations, taking into account the specific characteristics of cluttering, will also be presented. Finally, building clients' confidence, emotional skills, and sense of accomplishment will turn the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
1
6
0
5
Order By: Relevance
“…In the intergroup comparison of spontaneous speech, there were more differences in Non-Altered Auditory Feedback condition than in the delayed one (Tables 2). This result was already expected, once the main characteristic of cluttering is the increase in speech rate and the number of common disfluencies (2,6,7,8,9,10) . It is worth highlining that in the spontaneous speech under the DAF, the groups differed in the number of common disfluencies (Table 2).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In the intergroup comparison of spontaneous speech, there were more differences in Non-Altered Auditory Feedback condition than in the delayed one (Tables 2). This result was already expected, once the main characteristic of cluttering is the increase in speech rate and the number of common disfluencies (2,6,7,8,9,10) . It is worth highlining that in the spontaneous speech under the DAF, the groups differed in the number of common disfluencies (Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…In the description of the cluttering neurological foundations, a study concluded that the disorder may be explained by imbalance in the anterior cingulate cortex circuit and the supplementary motor area (5) . The main characteristics of cluttering are increased speech rate and excessive disfluencies (2,6,7,8,9,10) . Fast speech was reported both by studies that assessed speech rate (8,9) and compared it with normative standard (11) , as well as by reports of the own adults who clutter (1) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No large normative studies have been completed that reliably identify a specific number that defines “excessive” normal disfluencies and/or moments of over-coarticulation. In terms of abnormal pauses, two studies identified shorter mean pause duration in persons who cluttered (Rieber et al, 1972; van Zaaelen & Reichel, 2015). No work to date has been done examining the frequency of pauses in unexpected places in the speech of school-age children who clutter.…”
Section: Introductionmentioning
confidence: 99%